Povoljni učinci primjene ekstrakta kore nara na antropometriju i tjelesni sastav kod gojaznih dijabetes melitus tip 2 pacijenata: Randomizovana, dvostruko slijepa, placebo kontrolisana studija - Grabež, Milkica; Škrbić, Ranko; Stojiljković, Miloš; Rudić-Grujić, Vesna; Šavikin, Katarina; Menković, Nebojša; Zdunić, Gordana; Vasiljević, Nađa (Scripta Medica, 2020)
Background: Pomegranate is a rich source of a wide variety of polyphenol compounds with beneficial pharmacological activities for treating diabetes mellitus type 2 (DMT2). Most of DMT2 patients are overweight or obese and obesity by itself is linked to insulin resistance and abnormalities in insulin secretion. The aim of this study was to evaluate the effects of pomegranate peel extract (PoPEx) on anthropometry and body composition of overweight patients with DMT2.Methods: Sixty patients with DMT2 on continuous metformin therapy were recruited in this double-blind, placebo-controlled, randomized clinical trial. The study group (n=30) received capsules containing PoPEx (250 mg) twice a day for 8 weeks’ period, and the placebo group (n=30) received placebo capsules for the same period. Anthropometric characteristics (weight, waist circumference, fat mass percentage, visceral fat level) were measured at baseline and at the end of the study.Results: Eight weeks’ treatment with PoPEx resulted in significant changes in BMI (0.18 ± 0.30 kg/m2) and body mass (0.48 ± 0.93 kg). The intake of PoPEx produced a significant decrease in waist circumference z=-4.613, p